2014
DOI: 10.12659/msm.890098
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic imaging of the nasolacrimal drainage system. Part I. Radiological anatomy of lacrimal pathways. Physiology of tear secretion and tear outflow

Abstract: Excessive watering of the eye is a common condition in ophthalmological practice. It may be the result of excessive production of tear fluid or obstruction and insufficiency of efferent tear pathways. The differentiation between obstruction and insufficiency of the lacrimal pathways is still clinically questionable. In the diagnostic process it is necessary to perform clinical tests and additional diagnostic imaging is often needed. Dacryocystography, with or without the extension of the dynamic phase or subtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…According to previous studies, lacrimal scintigraphy, can identify treatment strategies for functionally acquired epiphora[ 13 , 14 ]. For example, a horizontal shortening of the lower eyelid may be present which can then augment the action of the lacrimal “pump” (as lower eyelid laxity has been associated with decreased lacrimal pump function[ 13 ]).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, lacrimal scintigraphy, can identify treatment strategies for functionally acquired epiphora[ 13 , 14 ]. For example, a horizontal shortening of the lower eyelid may be present which can then augment the action of the lacrimal “pump” (as lower eyelid laxity has been associated with decreased lacrimal pump function[ 13 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation was been acknowledged as the most important factor in the pathogenesis of DED [ 3 ]. The infiltration of a large number of lymphocytes in the lacrimal gland and ocular surface as well as the release of inflammatory cytokines can lead to immune-related inflammation, moreover, the production of inflammatory cytokines can damage the normal nerve conduction of tear secretion and affect the quality and quantity of tear secretion, forming a vicious circle [ 4 , 5 ]. A series of studies demonstrated that the levels of various cytokines including TNF-α, IL-1α, IL-1β, IL-6, IL-10, IL-8, and MIP-1α in tears of DED patients were significantly higher than those in normal people [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nasolacrimal ducts on the same patient side as the tumor were delineated following the definition by Maliborski et al [13], i.e., the interosseous portion of the nasolacrimal ducts and lacrimal sac ( Fig. 1).…”
Section: Dose-volume Analysis Of the Nasolacrimal Ductmentioning
confidence: 99%